STAGE: A compact and versatile TnpB-based genome editing toolkit for Streptomyces - Jing Luo; Natalie Chia; Yuxi Qin; Pan Tan; Lingwen Zhang; Sihan Yang; Zihan Yuan; Liang Hong; Sang Yup Lee; Yaojun Tong (Proceedings of the National Academy of Sciences, 2025)
Streptomyces are naturally endowed with the capacity to produce a wide array of natural products with biomedical and biotechnological value. They have garnered great interest in synthetic biology applications given the abundance of uncharacterized biosynthetic gene clusters (BGCs). However, progress has been hindered by the limited availability of genetic tools for manipulating these bacteria. Several representative CRISPR-Cas systems have been established in Streptomyces to streamline experimental workflows and improve editing efficiency. Nevertheless, their broader applicability has been constrained by issues such as nuclease activity-related cytotoxicity and the large size of effector proteins. To address these challenges, we present Streptomyces -compatible TnpB-assisted genome editing (STAGE), a genetic toolkit based on ISDra2 TnpB, which is approximately one-third the size of Cas9 and enables precise, site-specific gene editing. We demonstrated that STAGE introduces genetic mutations with high efficiency and minimal off-target effects in two industrially important Streptomyces strains. Building on this platform, we developed STAGE-cBEST and STAGE-McBEST, enabling single and multiplexed C·G-to-T·A base editing, respectively, with editing efficiencies exceeding 75%. To further enhance performance, we engineered the ISDra2 TnpB system using an AI-assisted protein engineering framework, resulting in two variants that achieve nearly 100% genome editing efficiency. Additionally, through sequence homology analysis, we identified a TnpB ortholog from the same biological origin of ISDra2 TnpB, which also functions effectively as a gene editing tool. Our study establishes STAGE as a highly precise, programmable, and versatile genome editing platform for Streptomyces , paving the way for advanced genetic manipulation and synthetic biology applications in these industrially important bacteria.